The Influence of Financial Literacy, Technological Advance, and the Development of Financial Technology (Fintech) on Students' Investment Decisions - Rosha Fitriyani; Dewi Sartika (Summa : Journal of Accounting and Tax, 2026)
This study seeks to examine the impact of financial literacy, technological advancements, and financial technology (fintech) developments on students' investment decisions. This research is driven by the importance of rational investment decision-making among the younger generation, especially students, who have great potential as future investors. This study uses a descriptive quantitative methodology, including an online questionnaire distributed to 105 active students of Bina Darma University. Data analysis was carried out using the SEM-PLS methodology through the SmartPLS 4.1.1.2 program. The research findings show that financial knowledge, technological advancements, and fintech innovations significantly influence students' investment choices. The study underscores the need to improve financial literacy, financial technology education, and improve self-efficacy among students to facilitate wiser investment decisions and reduce irrational investment risks. These findings are critical for educational institutions and fintech service providers to develop teaching programs that promote prudent and responsible investment practices.